Analisis Potensi Energi MatahariDan Pembangkitan Daya pada PLTSSebagai Sumber Rumah Energi Terbarukan Sederhana diKota Bengkulu - Dio Akbar Efriansyah; Afriyastuti Herawati; Ika Novia Anggraini; Reza Satria Rinaldi; Yuli Rodiah (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
With the location of Bengkulu Province on the west coast of Sumatra Island and facing the Indian Ocean, Bengkulu has good solar energy potential throughout the year so that it can be utilized as a simple renewable energy home source to increase energy independence in the community and energy security in a sustainable manner. In this study, a solar irradiation model approach was used through the equation developed by Bird and Hulstrom. This model considers the combined effects of aerosols, water vapor, ozone, air pressure, molecular scattering and other gases on sunlight reaching the earth's surface. The average total irradiation of 2.39 kWh/m2days and a total of 71.7 kWh/m2for 30 days were obtained. These results can be used as a renewable energy source for household consumption, the potential is sufficient. Power generation using 3 panels with an output of 286.5 Watts and an average of 244.5 Watts. Weather factors and solar irradiation affect these results. The charging time of a 100 Ah battery based on weather conditions, using 3 panels with cloudy sunny weather conditions was able to charge 100 Ah, a charging current of 14.55 Amperes with a charging time of 6.9 hours under ideal conditions and 7.6 hours under 10% efficiency loss conditions.